Risk assessment and risk management - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 1998)
Risk assessment is considered by many analysts to be an objective scientific tool. It is considered to be variously influenced by broader issues which in turn have important practical implications both for risk assessors and decision makers. Risk Assessment and Risk Management examines a range of practical applications of risk assessment methods and risk management procedures in the broad context of environmental science and technology. Written by acknowledged experts in the field, the articles cover a variety of areas, with reference to subjects as diverse as BSE, the use of risk assessment in government, using computer modelling as an aid to risk assessment in the case of accidental contamination of rivers and estuaries, quantitative cancer risk assessment related to carcinogens in the environment, landfilling of household wastes, environmental risk assessment and management of chemicals, and aquatic risk assessment and management of pesticides. This book provides a detailed and wide-ranging review of the many aspects of risk assessment and risk management which have excited so much debate and controversy in recent times. It will be essential reading for all those involved in the assessment and management of risk, particularly in the context of environmental science.
"Editors [of series], R.E. Hester and R.M. Harrison."
Keywords: Environmental risk assessment.; Risk management.; Environmental impact analysis.; Hazardous substances -- Management.; elektronické knihy; electronic books